Guide on Developing Climate-Smart Map and Adaptation Plan (CS-MAP) - Department of Crop Production; CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
An instructional video (in Vietnamese language) on how to develop and implement the Climate-Smart Map and Adaptation Plan (CS-MAP). Using participatory tools, CS-MAP serves as a guide for local communities to develop their own risk maps and adaptive plans, which cater to their respective local contexts.